Management’s Fiduciary Responsibility Towards IT Governance In The Context Of The King III Code Of Corporate Governance In South Africa - Mantey, Nicholas Otu (Advances in Social Sciences Research Journal, 2021)
The purpose of this study was to examine the extent to which South African listed companies trading on the Johannesburg Securities Exchange (JSE) are complying with IT governance imperatives in the context of the King III Code of Corporate Governance. Management information systems and usage of computers are now embedded in business processes to the extent that most firms will be dysfunctional should these tools become unavailable. The underlying theoretical setting for this study is anchored on the agency theory and the Porter’s competitive five forces model. Since there were inadequate constructs on the subject, a combination of research methods were used: desk-top review, exploratory study, and content analysis, by reviewing the annual financial statements of fifty JSE-listed companies (the main board) in South Africa. The general outcome of the study was that JSE-listed companies in South Africa were compliant with IT governance practices as prescribed in the King III Code of Corporate Governance. Most JSE-listed companies in South Africa utilized both generic and bespoke or owned-designed IT governance frameworks to meet IT governance requirements. The study also revealed that issues relating to IT governance were among priority issues for South African listed companies. The study concludes that JSE-listed companies in South Africa have indeed fulfilled their fiduciary responsibility towards IT governance.